Adoption of Green Technologies in the Industrial Sector: a Systematic Review of the Literature - Valencia Arias, Alejandro; Rodríguez-Correa, Paula Andrea; Ramón Ruffner de Vega, Jeri Gloria; Benjumea-Arias, Martha; Oré León, Aarón José Alberto (Rev. Téc. Fac. Ing. Univ. Zulia, 2023)
Green technologies have been consolidating as a contribution to the sustainable development of the industrial sector; however, little is known about the factors that affect the adoption of these technologies in this sector. Given this need, the objective of examining the factors associated with the adoption of green technologies in the individual and business context arises. The methodology was structured from a systematic review that follows the steps of the PRISMA methodology, from the search in the Scopus, Web of Science and Dimensions databases. The analysis of 123 documents was obtained as a result. Among the findings, it is observed that the relevant factors are the intention of use, social norms, attitude, and ecological awareness. It is concluded that the validation of these factors is necessary in the context of emerging economies, to establish strategies that respond to the needs of their social, technological, and economic context